The interplay of inflammation and remodeling in the pathogenesis of chronic rhinosinusitis: current understanding and future directions - Gong, Xinru; Han, Zhoutong; Fan, Hongli; Wu, Yuqi; He, Yuanqiong; Fu, Yijie; Zhu, Tianmin; Li, Hui (Frontiers in Immunology, 2023)
Chronic rhinosinusitis (CRS), a common clinical condition characterized by persistent mucosal inflammation and tissue remodeling, has a complex pathogenesis that is intricately linked to innate and adaptive immunity. A number of studies have demonstrated that a variety of immune cells and cytokines that play a vital role in mediating inflammation in CRS are also involved in remodeling of the nasal mucosa and the cells as well as different cytokines involved in remodeling in CRS are also able to exert some influence on inflammation, even though the exact relationship between inflammation and remodeling in CRS has not yet been fully elucidated. In this review, the potential role of immune cells and cytokines in regulating inflammation and remodeling of CRS mucosa has been described, starting with the immune cells and cytokines that act together in inflammation and remodeling. The goal is to aid researchers in understanding intimate connection between inflammation and remodeling of CRS and to offer novel ideas for future research.